2013
DOI: 10.4103/0019-509x.117029
|View full text |Cite
|
Sign up to set email alerts
|

Can combination metronomic therapy overcome chemoresistance in cholangiocarcinoma? A literature review

Abstract: Cholangiocarcinoma (CCa) is relatively resistant to chemotherapy as well as radiation therapy, and complete resection is the main curative therapy for these patients. The prognosis for patients with unresectable intrahepatic CCa (iCCa) is extremely poor. A 55-year-old woman presented at our hospital with abdominal pain. After evaluation, she was diagnosed to have multifocal iCCa. She did not opt for standard chemotherapy and therefore received oral metronomic therapy with a combination of celecoxib, etoposide,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Banavali et al, [25] from the Tata Memorial Hospital outreach center reported an interesting case of cholangiocarcinoma who underwent first line palliative care with a metronomics combination of celecoxib, cyclophosphamide and etoposide. This treatment led to a progressive response and ultimately a complete remission after 1 year of treatment.…”
Section: Pmidmentioning
confidence: 99%
“…Banavali et al, [25] from the Tata Memorial Hospital outreach center reported an interesting case of cholangiocarcinoma who underwent first line palliative care with a metronomics combination of celecoxib, cyclophosphamide and etoposide. This treatment led to a progressive response and ultimately a complete remission after 1 year of treatment.…”
Section: Pmidmentioning
confidence: 99%